OPTIMALISASI PENGGUNAAN RUANG PARKIR PADA FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS DIPONEGORO - Rina Syamsurizal; Agung Budi Setiyawan; Bambang Pudjianto; Rudi Yuniarto Adi (Jurnal Karya Teknik Sipil, 2013)
Faculty of Public Health is one of faculty in Diponegoro University which is inseparable from parking problems. Due to increasing the number of students and vehicles ownership, the parking space requirements are exceed its capacity. To determinate the parking space unit (SRP) using Pedoman Teknis Penyelenggaraan Fasilitas Parkir,1996. Current parking capacities based on SRP are 242 vehicles for students motorcycles, 37 vehicles for cars, and 32 vehicles for employees and lecturers motorcycles. Parking space requirements based on the survey results and analysis are 360 vehicles for students motorcycles, 18 vehicles for cars and 36 vehicles for employees and lecturers motorcycles. To reach the parking demands, it shall need several steps of optimization. The first  step is  rearranging parking configuration based on parking space requirements according to survey results. After parking configuration setup, parking space requirements have not been fullfilled. The second step is class rescheduling. It's needed in  order to get optimal parking demands. After class rescheduled, parking space requirements for students motorcycles became 310 vehicles. To solve the problem of parking space requirements which exceed its capacity, it is necessary to restructure or change the configuration of the parking supplies in an optimal order capacity of parking spaces to serve the parking demands. Optimize the configuration of parking spaces by changing the functionality of some of  cars parking to motorcycles parking thus the parking space being adequate.